Interlaboratory comparison of liquid chromatography-tandem mass spectrometry quantification of diarrhetic shellfish toxins in scallop midgut glands. (30th June 2018) - Yarita, Takashi; Inagaki, Shinsuke; Yamazaki, Taichi; Kawaguchi, Migaku; Uchida, Hajime; Takatsu, Akiko; Suzuki, Toshiyuki
Highlights: Interlaboratory comparison for LC-MS/MS quantification of diarrhetic shellfish toxins in Japanese scallop midgut glands. Test samples were prepared from naturally contaminated scallops spiked with okadaic acid. Assigned values based on the standard addition method were appropriate. Sufficient accuracy of the Japanese official testing method was demonstrated. Abstract: An interlaboratory comparison (ILC) was organized as a measure of the analytical competency in the liquid chromatography-tandem mass spectrometry quantification of okadaic acid (OA) and dinophysistoxin-1 (DTX1) in scallop midgut gland samples. The test sample was prepared using boiled midgut glands of naturally contaminated scallops with DTX1 and its esters by spiking with OA, and homogeneity and stability of this test sample was assessed to be appropriate. Twenty laboratories participated in the ILC based on the Japanese official testing method; they submitted two sets of analytical concentrations of target analytes along with the details of their analytical protocols. For assessing these data, assigned values were established from another ILC where ten participants quantified the target analytes by the standard addition method. The mean analytical results of the former ILC showed good agreement with the assigned values, and the corresponding relative reproducibility standard deviations met the criterion of CODEX STAN 292. Meanwhile, the results of more than half of the participants were out of the uncertainty range of the assigned values; these participants were encouraged to investigate their protocols to improve their analytical capability.